Investigating the liberation method of interreligious dialogue as a common ground for Muslim-Christian relations in Northern Nigeria - Salihu, Joseph Patrick (Irish School of Ecumenics, 2004)
This dissertation investigates the relevance of the liberation method of interreligious dialogue as a common ground for Muslim-Christian relations in Northern Nigeria. The region of our study is one characterised by the existence of two dominant religions: Islam and Christianity, and also one plagued by poverty. It therefore constitutes a good laboratory for testing the efficacy of the liberation method. This is undertaken to show the dynamics that facilitate interreligious encounter, employing a balance of theoretical and empirical presentations.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin